Tuberculosis bovina : transmisibilidad de cepas de Mycobacterium bovis y detección de micobacterias en menudencias comercializadas en bocas de expendio de carne - Marfil, María Jimena (2019)
Bovine tuberculosis, a disease caused by Mycobacterium bovis (M. bovis), is endemic\nin Argentine. Its presence in cattle represents a risk to human health, due to its\nzoonotic nature and can also affect various mammals. In human beings, M. bovis\ncauses disease with pulmonary or extrapulmonary presentation, being the clinical manifestation undistinguishable from that produced by M. tuberculosis. The most exposed are children who consume unpasteurized milk or its products, adults who\nworks with livestock and also hunters. To avoid the arrival of the agent to the\nconsumer, one of the main barriers of protection are the carcasses post-mortem\ninspection at the slaughterhouse, to detect and confiscate organs with lesions compatible with tuberculosis or even the hole animal. Inspection is performed visually\nand by palpation of the bovine organ, but due to the pathogenesis of the\nMycobacterium, only the chronic lesions can be evidenced in this inspection. The Mycobacterium might be present even in tissues without apparent lesion, being the lymph nodes and the lungs, the most affected organs: Other parenchymal organs such as the liver could also be affected. This can lead to escapes of the surveillance system\nallowing the Mycobacteria to reach the stores and hence, arrive to the consumer.\nIn this study, 210 lungs along with the corresponding lymph nodes and 6 bovine livers were collected, in one slaughterhouse and 6 butchers´ shops in the city of Buenos Aires and the great Buenos Aires area. The lungs collected in the slaughterhouse were\ninspected in situ and small portions of them were taken. Complete lungs and livers that were bought in butchers´ shops and were then inspected in the laboratory.\nA total of 5 isolates of M. bovis were obtained in Stonebrink medium and its identity confirmed by PCR IS-6110 (isolates number 134, 719, 179, 182 and 184). Additionally\n12 non-tuberculous mycobacteria were isolated and confirmed by the sequencing of the hsp65, rpoB and 16S rRNA genes. The isolates of M. bovis were molecularly\ncharacterized by Spoligotyping and MIRU-VNTR. We could differentiate 3\nSpoligotyping patterns that corresponded with the 3 patterns of MIRU-VNTR obtained. Three isolates shared both patterns and the other 2 were unique. Additionally, drug\nresistance to human treatment commonly used drugs (rifampicin, isoniazid,\nethionamide, levofloxacin and streptomycin) was investigated in all M. bovis isolates, and it was found that isolate number 184 was resistant to isoniazid and isolate number 134 was multi-resistant (showing resistance to the 4 antibiotics tested and considered "border" for levofloxacin). One non-tuberculous mycobacteria isolates from which good\nquality DNA was obtained was completely sequenced (whole genome equencing).\nThe genome was annotated and its characteristics were investigated as well as the \npresence of single nucleotide polymorphism (SNPs) in virulence genes and genes\nrelated to resistance to antibiotics and antigens used for diagnosis.\nThe virulence and transmissibility of isolates number 134 and 182 were evaluated together with a reference strain M. bovis-AN5 (considered of intermediate virulence), in\nan experimental assay in a mouse model. A total of 99 BALB/c female mice aged 5\nweeks, were separated in 3 groups of 33 animals each. In turn, each group was divided into 6 cages, the first cage with 3 animals and the remaining cages with 6 animals. All animals in cage number 1 of each group and 3 from each of the remaining cages, were intratracheally inoculated under sedation with isoflurane, with 1x105 CFU of each of the strains to be evaluated, suspended in 100 ?L of PBS, keeping the relationship between\ninoculated animal and healthy contact 1:1. Virulence was evaluated in those animals that were inoculated, while in the healthy contacts that were living with the infected\nanimals the transmissibility of the strains was investigated. Euthanasia of 5 infected animals and 5 healthy contact animals of each group were performed at times 30, 60 and 90 days post-inoculation. The lungs and spleens of all infected animals and healthy contacts were cultured. The cultures were grown at 37°C for up to 2 months, with weekly evaluation of their growth. Spleens were further processed to measure the\ncytokines IL-4, TNF? and INF? with the use of a commercial Cytometric bead array kit. Strain number 134 showed to be virulent because it produced symptoms incompatible\nwith life on day 16 after inoculation, producing the death of 9 animals, the remaining 6 were euthanatized and processed. Strain number 182 generated spleen enlargement in the infected mice, but it did not generate the illness or death of any of them. The transmissibility of strain 182 could be evidenced, due to the observation of the growth\nof colonies from a spleen of a contact animal in the time of euthanasia 90 days after\ninoculation It was possible to detect the presence of both, zoonotic and environmental\nmycobacteria, in commercialized viscera. The virulence, transmissibility and drugresistance of the M. bovis strains was variable, requiring future studies for a better understanding of the dynamics of the disease.